Associations between changes in frailty status and non-neoplastic digestive system diseases: A cohort study based on the China health and retirement longitudinal study - Jingwei Che; Qiao Song; Chunyu Zhao; Yuan Yuan; Xiaohua Lyu (Experimental Gerontology)
Background: While prior studies have linked baseline frailty to specific non-neoplastic digestive diseases (NNDSD), the impact of frailty status transitions remains understudied. Method: Participants were sourced from the China Health and Retirement Longitudinal Study (CHARLS) and categorized as robust, pre-frail, or frail using a frailty index comprising 32 health deficits with thresholds of 0.10 and 0.25. The frailty status at initial follow-up served as the baseline, and transitions were assessed using changes between the first and second follow-ups. NNDSD was defined based on patients' self-reports of whether a physician diagnosed them with a relevant disease. Associations between baseline frailty status, frailty transitions and NNDSD were assessed using Cox proportional hazards modeling. Finally, multiple sensitivity analyses were performed to validate result robustness. Results: A total of 6994 participants (41 % women) were included in the baseline. Participants classified as pre-frail (hazard ratio [HR]: 1.55, 95 % confidence interval [CI]: 1.38–1.75) and frail (HR: 2.39, 95 % CI: 1.99–2.89) exhibited elevated NNDSD incidence. The final sample comprised 5299 participants (41 % women). Progression to pre-frail (HR: 1.64, 95 % CI: 1.30–2.10) and frail (HR: 2.91, 95 % CI: 1.72–4.90) was associated with NNDSD risk relative to participants who remained robust. Progression from pre-frail to frail (HR: 1.39 95 % CI: 1.08–1.81) elevated the risk of NNDSD onset. Recovery from pre-frail to robust (HR: 0.73, 95 % CI: 0.57–0.94) was associated with reduced NNDSD risk, with sensitivity findings corroborating study robustness. Conclusions: Changes in frailty status were positively associated with new-onset NNDSD risk. Frailty progression corresponded to elevated risk, whereas reversal was linked to risk reduction.